How is animal welfare internalized in consumers’ purchase decision? : a means-end chain analysis - Palmér, Marie; Humble, Maria (SLU/Dept. of Economics, 2018)
As a consumer, the choice of what food to buy can be rather challenging due to the great supply of items and each item’s set of various product attributes. Consumer behavior is often viewed as goal-oriented, and by choosing a specific product or brand, the consumer will satisfy or achieve his or her broad life goal - a symbolic, personal value. In our food consumption, meat is a central element, and is often related to the “meat paradox”; most people enjoy eating meat but also care for animals’ wellbeing. The ethical consumption has been up for discussion, with questions about what is right or wrong to purchase and consume in a moral sense. Particularly the animal welfare aspect of pork has been discussed because of the differences in the legislation of animal protection among countries. Research about consumers’ purchase decision has emphasized that consumers express a concern that the welfare of farm animals are protected. However, these studies did not investigate how the concern for farm animal welfare is related to underlying values, or which these values are. These results have also been obtained by methods where consumers give answers based on simulated shopping experiences. Though, when individuals are standing in the grocery store and making purchase decisions in the role of consumer, the connection between their stated attitudes and concerns, and their true purchase behavior is not always consistent. Thus, one cannot be sure that people’s reported views on farm animal welfare appear when they select meat in a real purchase situation. This study aims to explore how animal welfare is internalized in consumers’ purchase decision and what personal values influence the decision when selecting animal-based food products. It is assumed that it is the personal values that motivate choosing a certain product with its certain attributes. By using Personal value theory, Means-end chain theory and Laddering interviews conducted at the point of purchase, we can obtain the true reasons for consumers purchase behavior. Through our method, we are able to find what values influencing the decision and obtain answers from the respondents in their role as consumers and not as citizens. The result from this study indicates that animal welfare is not the most salient element in our respondents’ purchase decision of pork. The results demonstrate that when selecting a specific pork fillet, almost half of the respondents expressed the product’s price as the primary mean to reach their desired end state; having money for other things. Around one third of the respondents had farm animal welfare in their minds to reach their desired end state; feeling good or acting ethically. We can conclude from this study that our respondents prioritize their own comfort before the welfare of the animals. It is also possible to conclude that the overall most salient personal value types that influence the purchase decision of pork are; Hedonism, Security, Benevolence, and Universalism.